Mitigation techniques for autogenous shrinkage of ultra-high-performance concrete – A review. (1st December 2019) - Yang, Li; Shi, Caijun; Wu, Zemei
Abstract: Ultra-high-performance concrete (UHPC) demonstrates relatively high autogenous shrinkage at early age due to the use of high binder content and low water-to-binder ratio of approximately 0.2. High shrinkage can result in potential cracking and eventually reduced strength and durability of concrete. Several approaches can be used to mitigate the autogenous shrinkage based on restraining mechanism. These include (1) control of hydration reaction; (2) addition of internal restraint; (3) reduction of the surface tension of pore solution; (4) formation of expansive products; and (5) replenishment of water through internal curing. This paper reviewed those mitigation techniques from the perspective of restraining mechanism and influential factors. Finally, the advantages and disadvantages of those techniques were compared. It is indicated that internal curing is the most straightforward and effective approach to reduce autogenous shrinkage of UHPC. The combination of two and/or more techniques can simultaneously exert their functions, and thus maximizing the restraining effectiveness.